Ultra-Morphological Changes of Trichophyton Rubrum Treated with Hydroxychavicol - Ridzuan, P. M.; Mohamad, Nasir; Ismail, Salwani; Rahman, Nor Iza A.; N.A, Sanusi; Umar, Rabiatul Adawiyah; Hamzah, Hairul Aini; B., Zunariah; Norazian, M. H.; Roesnita, Baharudin (IIUM Medical Journal Malaysia, 2017)
Trichophyton rubrum is a common pathogenic fungal species that is responsible for causing infection on human skin, hair and nail. The antifungal-resistant strains complicate the treatment regime. Hydroxychavicol (HC) is one of the main compounds from Piper betel leaf that have antifungal potential and its mechanism of action has not been studied yet. The objective of this preliminary study to determine the antifungal properties of HC against T. rubrum using transmission electron microscope (TEM) on gross and ultrastructure of T. rubrum hypha. T. rubrum was treated with HC and miconazole (MI) at concentrations of 1.25, 2.5, 5 and 10 mg/mL for 1, 3, 5 and 7 days continuously. Generally, fungi structures became more severely damaged at increasing treatment duration. Microscopically, the fungi’s cell wall treated with HC showed a rough surface, shrinkage and demolition similar to the MI treated group. The fungi organelles were also demolished and disorganized. This study revealed that HC has the ability to inhibit T. rubrum growth and has potential to be an antifungal agent for skin infections.